2006
DOI: 10.2460/ajvr.67.11.1844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of width of disk fenestration and a ventral slot on biomechanics of the canine C5-C6 vertebral motion unit

Abstract: Analysis of these results suggests that fenestration and ventral slot procedures each affect the biomechanics of the C5-C6 VMU. Width of a fenestration or ventral slot up to 50% of the width of C5-C6 may be clinically acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 14 publications
3
28
1
Order By: Relevance
“…Our study confirmed that a lateralized disc herniation can be removed trough a ventral slot centered on the midline. These data are consistent with the results of a previous study on ventral slot decompression surgery by Böttcher et al In our study, the dimensions of the ventral slot were smaller than the safe limits recommended: 33% of the vertebral body length and 30–50% of the vertebral body width . Residual extradural compression in our study seemed to be less frequent (57% of cases) when compared to a previous study by Böttcher et al (77% of cases) .…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirmed that a lateralized disc herniation can be removed trough a ventral slot centered on the midline. These data are consistent with the results of a previous study on ventral slot decompression surgery by Böttcher et al In our study, the dimensions of the ventral slot were smaller than the safe limits recommended: 33% of the vertebral body length and 30–50% of the vertebral body width . Residual extradural compression in our study seemed to be less frequent (57% of cases) when compared to a previous study by Böttcher et al (77% of cases) .…”
Section: Discussionsupporting
confidence: 92%
“…They demonstrated a significant increase in flexion/extension range of motion post surgery indicating that these procedures may have a destabilizing effect of the involved segment [8, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…cage, prosthesis or bone grafts) as done routinely in humans [11]. Removal of the disc and subsequent altered segmental functionality [8, 10, 12] could enhance degenerative changes [9, 13], which is why several authors advocate not to perform discectomies especially for prophylactic purposes [14, 15]. However, the correlation of discectomy procedures and segmental degenerative changes is somewhat hypothetical as it has not been studied in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Several technical modifications have been suggested to mitigate the risks associated with ventral slot surgery . The inverted cone and slanted slot techniques are intended to minimize the amount of bone removal, therefore reducing the risk of intraoperative hemorrhage and postoperative vertebral subluxation.…”
mentioning
confidence: 99%
“…The inverted cone and slanted slot techniques are intended to minimize the amount of bone removal, therefore reducing the risk of intraoperative hemorrhage and postoperative vertebral subluxation. Creation of the slot within well‐defined margins and strict centering of the slot over sagittal midline are also considered important precautions to minimize the potential for inadvertent trauma to the vertebral venous sinus . Regardless of the technical modification, the recommended approaches for ventral slot surgery all require bone removal using a motorized burr (MB) .…”
mentioning
confidence: 99%